2016
DOI: 10.1016/j.jphotochem.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties of Re(I)(CO)3(phen) pendants grafted to a poly-4-vinylpyridine backbone. A correlation between photophysical properties and morphological changes of the backbone

Abstract: Photochemical and photophysical properties of a polymer, Re-P4VP, consisting of -Re(I)(CO)3(phen) pendants grafted to a poly-4-vinylpyridine backbone, P4VP, were interpreted on the bases of morphological transformations. These transformations are responsible of a significant increase of the MLCTRe(I) → phen excited state luminescence lifetime when the polymer concentration is increased. Also a nearly 8-fold increase in the luminescence quantum yield resulted from the protonation of Re-P4VP with consequent chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…When a deaerated solution of poly-I in CH 3 CN is irradiated at λ exc = 350 nm, the characteristic luminescence of pendants -Re(CO) 3 phen + chromophores showing a broad unstructured band centered at λ max = 550 nm is observed. In this work, 45 a complementary study to the previous one in the literature, 42 it has been established that the luminescence lifetime of excited -Re(CO) 3 phen + pendant chromophores in poly-I is dependent on the polymer concentration. Luminescence lifetimes were calculated from traces obtained with polymer concentrations corresponding to a total chromophore concentration varying from [Re] = 2 x 10 -5 M to 4 x 10 -4 M. In the range of [Re] = 2 x 10 -5 M to 1 x 10 -4 M, a sum of two exponential functions was needed, with lifetimes τ em,1 and τ em,2 to fit the luminescence decay profiles.…”
Section: A Correlation Between Backbone Photophysical Properties and Morphological Changes In Poly-imentioning
confidence: 78%
See 3 more Smart Citations
“…When a deaerated solution of poly-I in CH 3 CN is irradiated at λ exc = 350 nm, the characteristic luminescence of pendants -Re(CO) 3 phen + chromophores showing a broad unstructured band centered at λ max = 550 nm is observed. In this work, 45 a complementary study to the previous one in the literature, 42 it has been established that the luminescence lifetime of excited -Re(CO) 3 phen + pendant chromophores in poly-I is dependent on the polymer concentration. Luminescence lifetimes were calculated from traces obtained with polymer concentrations corresponding to a total chromophore concentration varying from [Re] = 2 x 10 -5 M to 4 x 10 -4 M. In the range of [Re] = 2 x 10 -5 M to 1 x 10 -4 M, a sum of two exponential functions was needed, with lifetimes τ em,1 and τ em,2 to fit the luminescence decay profiles.…”
Section: A Correlation Between Backbone Photophysical Properties and Morphological Changes In Poly-imentioning
confidence: 78%
“…The shorter lifetime, τ em,1 = 55 ± 7 ns, remains essentially constant between 2 x 10 -5 M and 1 x 10 -4 M, while the longer lifetime, τ em,2 , increased monotonically from 240 to 490 ns. When [Re] > 1 x 10 -4 M, the luminescence decay was fitted without deviation to a single exponential with a lifetime τ em = 581 ± 10 ns, which is independent of polymer concentration in the concentration range 1 x 10 -4 M < [Re] < 4 x 10 -4 M. TEM and AFM studies 45 on poly-I and its protonated form, poly-IH n n+ , have shown that (i) the morphology of Re-P4VP polymers is concentration-dependent and (ii) protonation of poly-I polymers alters strongly their morphology. Hereafter, the polymer concentration will be expressed in chromophore units, i.e.…”
Section: A Correlation Between Backbone Photophysical Properties and Morphological Changes In Poly-imentioning
confidence: 99%
See 2 more Smart Citations
“…In the last two decades, we have focused our research interests on the study of the photochemical and morphological properties of Re­(I) polymeric complexes. The polymers used in our works have been derived from the P4VP backbone, and they contain fac -XRe­(CO) 3 L pendants in their structure. The Re­(I) polymers are polyelectrolytes where Re­(I) center coordinates one of every three pyridines present in the P4VP. They display interesting as well as intriguing features both in photochemistry and in material science.…”
Section: Introductionmentioning
confidence: 99%